Models for quantitative structure-toxicity relationships of various carbamates - Baja, Emmanuel Saporna (2003)
Quantitative structure-toxicity relationships (QSTR) were studied for 43 carbamate insecticides derivatives by methods of multiple linear regression (MLR) and nonlinear regression (NR). Ninety (90) models with 16 to 32 descriptors were manipulated in this study. The best model, its methods and modifications, was used to theoretical predict the LD50 toxicity of some carbamate insecticides. The results obtained in this study are significant and important for the synthesis of new organic insecticides.